Qualidade fisiológica e sanitária de sementes de soja ozonizadas durante a secagem - Rego, Joemar Mendes (2017)
In Brazil, soybeans are considered one of the main agricultural products, however, with the expansion of agriculture, new phytosanitary diseases have emerged. Thus, inadequate storage can lead to the growth of insects and microorganisms as well as promote product deterioration. Currently, ozone gas is among the products being studied for the disinfection of fungi, which is formed by three molecules of oxygen (O3) and its final product is oxygen. In addition, O3 is considered safe by the food industry. Thus, the objectives of this study were to evaluate both the effects of ozone gas during drying in terms of physiological and physical-chemical quality, as well as the efficiency of fungal decontamination and to determine the modeling of drying curves for soybean seeds. For this study, seeds of cultivar NK 7059 (V-máx RR), produced in the Medianeira-PR region, from the 2016 crop with 20.18% B.U. A factorial design 22 with center point was used, with times (5, 10 and 15 minutes) and temperature (30, 40 and 50 ° C). The mathematical model that presented the best fit to the experimental data was Midilli. The coefficients a, b and k were considered to be dependent on the drying air temperature while the coefficient n was dependent on the time factors of ozone application and drying air temperature. Ozone gas demonstrated efficiency in fungal decontamination through microbiological effects and the temperature of 50 °C showed the best results. The time of five minutes of ozone application and the air temperature of 30 °C for drying showed a higher number of germinated seeds.